Pengaruh Motivasi Dan Beban Kerja Terhadap Kinerja Karyawan Pada PT. Pelni (persero) Cabang Makassar - Firmansyah Firmansyah; Arkah Septiono (P3M STIEM BONGAYA, 2022)
This study is to examine and analyze the effect of motivation on employee performance, the effect of workload on employee performance and the simultaneous influence of motivation and workload on employee performance.Collecting data using primary data obtained from employees At work at PT. Pelni (PERSERO) Makassar branch where sampling uses saturated samples where all populations are sampled. The results of the primary data collected through the distribution of the questionnaire have been tested with classical assumption tests in the form of normality assumptions, multicollinearity assumptions and heteroscedasticity assumptions. The data analysis method uses descriptive statistical analysis techniques and inferential statistical analysis. The results showed that both partially positive and significant motivation had a positive and significant effect on employee performance, workload had a significant negative effect on employee performance, simultaneously motivation and workload had a positive and significant effect on employee performance so that all proposed hypotheses were accepted.